2015
DOI: 10.1111/ejh.12563
|View full text |Cite
|
Sign up to set email alerts
|

Mean reticulocyte volume: a specific parameter to screen for hereditary spherocytosis

Abstract: This study assessed the value of mean reticulocyte volume (MRV) for differential diagnosis of hereditary spherocytosis (HS) so as to develop conventional and new specific screen indexes. Subjects in this study were divided into three groups: 53 cases in HS group, 217 cases in hemolytic anemia control group (109 cases of thalassemia (THAL), 56 cases of glucose-6-phosphate dehydrogenase G6PD deficiency anemia, and 52 cases of autoimmune hemolytic anemia (AIHA)), and 100 cases in healthy control group. We analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…MRV ≤ 96.72 fl had a diagnostic sensitivity and specificity of 100% and 88%, respectively. We previously compared blood cell parameters among patients with HS, THAL, AIHA, and G6PD deficiency and identified MRV as a general and specific index for HS screening and for the differential diagnosis of different types of hemolytic anemia . We also found that MRV ≤ 95.8 fl had a diagnostic sensitivity and specificity of 86.8% and 91.2%, respectively.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…MRV ≤ 96.72 fl had a diagnostic sensitivity and specificity of 100% and 88%, respectively. We previously compared blood cell parameters among patients with HS, THAL, AIHA, and G6PD deficiency and identified MRV as a general and specific index for HS screening and for the differential diagnosis of different types of hemolytic anemia . We also found that MRV ≤ 95.8 fl had a diagnostic sensitivity and specificity of 86.8% and 91.2%, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Mean corpuscular hemoglobin concentration (MCHC) was included as one of the diagnostic criteria for HS in guideline for the diagnosis and management of HS in 2004, and mean sphered corpuscular volume (MSCV) has also been reported to have diagnostic value in HS . Furthermore, we recently found that mean reticulocyte volume (MRV) was a valuable index for the diagnosis of HS . In this study, we investigated the values of blood cell parameters including MRV, MSCV, MCHC, and absolute reticulocyte count (Ret)/immature reticulocyte fraction (IRF) for the screening and differential diagnosis of HS.…”
Section: Introductionmentioning
confidence: 99%
“…This approach may be suitable for some HS patients with mild clinical symptoms and can be consi­dered a new standard for HS diagnosis. Nevertheless, recent studies have verified that mutations in SLC4A1 and SPTA1 are not specific to HS patients [4, 48, 49]. To identify different types of hemolytic anemia and hepatitis, clinical histories and laboratory tests are needed [3, 4, 48-51].…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…The value of MRV in the screening of HS was first reported by Lazarova et al (19) in 2014, where they demonstrated that MRV ≤96.72 fl showed 100% sensitivity and 88% specificity for the diagnosis of HS. Moreover, in a study performed on 53 HS patients, 109 thalassemia patients, 56 G6PD deficiency patients, and 52 AIHA patients by Xu et al (20) it was demonstrated that MRV ≤95.77 fl showed 86.8% sensitivity and 91.2% specificity for the diagnosis of HS. The limitations of basic hospitals and insufficient knowledge of clinicians towards HS were the main reasons for misdiagnosis of the proband.…”
Section: Discussionmentioning
confidence: 97%